Implementing a Challenge-Based Ethnoscience E-Book on Colloid Systems to Enhance Students’ Critical Thinking and Conceptual Understanding - Sjaeful Anwar; Bagas Abdurachman; Ijang Rohman; Shiang-Yao Liu; Harianti Harianti (Universitas Negeri Semarang, 2026)
Colloid learning is often difficult for students to relate to real-world phenomena, leading to a lack of conceptual understanding and critical thinking skills. One relevant local context for concretizing the concept of colloids is tofu waste treatment, which involves colloidal systems and environmental issues in the community. Integrating this ethnoscience context through Challenge-Based Learning has the potential to provide more contextual, meaningful, and authentic learning oriented toward problem-solving. This study aims to develop and demonstrate the impact of a Challenge-Based Ethnoscience e-book about colloids in the context of tofu waste treatment on improving students' conceptual understanding and critical thinking skills. This research method used Design and Development Research, consisting of three phases: design (needs analysis and product design), development (based on the 4STMD model), and evaluation (Students' critical thinking and conceptual understanding). Implementation was conducted with 30 eleventh-grade students. Critical thinking skills were measured using the Ennis framework, while conceptual understanding was assessed through context-based essay questions. Data were analyzed using the Wilcoxon test, Spearman correlation, and rank-biserial effect size. Results showed significant improvements in conceptual understanding and critical thinking skills, indicating consistent positive score changes across all participants. A very strong correlation was found between conceptual understanding and critical thinking skills, indicating a high degree of shared variance between the two. It can be concluded that the CBL e-book on ethnoscience related to colloid materials, developed according to the 4STMD, is a feasible and effective learning material for chemistry. This learning material aligns with the learning curriculum, is scientific, and organizes materials systematically through local wisdom, specifically in the context of tofu wastewater treatment, to enhance students' understanding of concepts and critical thinking skills.